A child with solitary thyroid nodule: What’s next? - Mohamad, Adam; Yusuf, Suhaimi; Mohamad, Irfan (International Journal of Human and Health Sciences (IJHHS), 2019)
Paediatric thyroid nodule is a rare occurrence. It occurs about 1.5% in childhood while 4-7% in adulthood. The presentations include anterior neck swelling which moves with deglutition. The treatments of choice are either conservative treatment or complete surgical excision if there is presence of obstructive symptoms or malignancy. We describe an 8-year-old girl presented with left solitary thyroid nodule. Malignancy must be ruled out before conservative management was instituted. International Journal of Human and Health Sciences Vol. 04 No. 01 January’20 Page : 70-72